Application of sensitive quality indicators of assembly for medical instruments in quality management of Central Sterile Supply Department (器械装配质量敏感指标在消毒供应中心质量管理中的应用) - ZHANG Ying (张颖); ZHANG Xiaorong (张晓蓉); CAO Lixia (曹丽霞) (中西医结合护理)
Objective To investigate the effect of sensitive quality indicators on quality management of assembly for medical instruments in Central Sterile Supply Department (CSSD). Methods The error rate of assembly was set as an sensitive quality indicator, and root-cause analysis was made to find influencing factors in issues of human resource, instruments, process and methods. The standard operation procedure was established and countermeasures such as personnel training and information technology support were carried out. The error rates of assembly for medical instruments processed in Central Sterile Supply Department after implementation of sensitive quality indicators (between January and September 2020) were collected and compared with those before implementation of sensitive quality indicators (between January and September 2019). Results The error rate of assembly dropped from 0. 020% to 0. 006%. The implementation of sensitive quality indicators had shortened the time cost in assembling instruments and reduced the man-time of changing shift. Conclusion The establishment of sensitive quality indicators makes the work in CSSD more standardized and qualified, and provide scientific evidence for quality assessment and monitoring. (目的 探讨质量敏感指标管理模式应用于器械装配质量改善的效果。方法 通过将“装配错误率”作为评价器械装配质量的敏感指标, 对器械装配错误从人员、物品、流程、方法等环节进行查检找出根本原因, 建立质控标准, 实施标准化管理, 多形式开展人员培训, 以及信息技术支撑等改进措施。 对2020年1月—9月(实施后)经消毒供应中心处理的无菌包进行包装检查, 收集器械装配错误率等相关信息, 并与2019年1月—9月(实施前)经消毒供应中心处理的无菌包的相关信息进行对比。结果 实施质量敏感指标管理模式后, 科室器械装配错误率由实施前的0. 020%下降至实施后的0. 006%。单包器械平均配包时间缩短, 人员临时调班次数降低。结论 专科质量指标的实施, 使消毒供应中心的工作更加规范化、标准化, 提高了消毒供应中心的工作质量, 为消毒供应中心护理质量评价与监测提供了科学依据。)